2017
DOI: 10.1002/ieam.1994
|View full text |Cite
|
Sign up to set email alerts
|

The utility of solid‐phase microextraction in evaluating polycyclic aromatic hydrocarbon bioavailability during habitat restoration with dredged material at moderately contaminated sites

Abstract: The over- or underprediction of risk in moderately contaminated sediments can have a large impact on the nature of applied management strategies given that concentrations border on being toxic or not toxic. Project managers should give significant consideration as to how moderate levels of contaminants in native sediments and dredged material used for restoration will impact recovery of habitat. Total solid-phase (C ) and porewater (C ) polycyclic aromatic hydrocarbons (PAHs) were quantified in native sediment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…However, the data were from 9 different sites, and using a single K BC across sites is inconsistent with data from Hawthorne, Grabanski et al (), which showed that measured K BC values for individual PAHs vary by more than 2 orders of magnitude across different sites. These results are consistent with a field study by Brennan and Johnson () who found improved estimates of PAH toxicity and bioaccumulation were observed with the 2‐C model compared to the 1‐carbon (1‐C) model, highlighting the importance of BC and the limitations of using a 1‐C phase model to describe PAH partitioning. Nevertheless, dissolved porewater predictions derived using the 2‐C model overpredicted the importance of BC partitioning in some sediments.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, the data were from 9 different sites, and using a single K BC across sites is inconsistent with data from Hawthorne, Grabanski et al (), which showed that measured K BC values for individual PAHs vary by more than 2 orders of magnitude across different sites. These results are consistent with a field study by Brennan and Johnson () who found improved estimates of PAH toxicity and bioaccumulation were observed with the 2‐C model compared to the 1‐carbon (1‐C) model, highlighting the importance of BC and the limitations of using a 1‐C phase model to describe PAH partitioning. Nevertheless, dissolved porewater predictions derived using the 2‐C model overpredicted the importance of BC partitioning in some sediments.…”
Section: Resultssupporting
confidence: 90%
“…Furthermore, the development of guidance for the use of passive sampling methods and standard protocols is leading to their growing use in site risk evaluations and acceptance by regulating agencies (USEPA 2017b). Consistent with the conclusions of Brennan and Johnson (2017), the use of direct porewater measurements determined through passive sampling techniques provides the logical path forward for refining benthic risk assessments, establishing improved remediation goals to protect benthic life, and assessing remedial effectiveness. preparation.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Because no black carbon measurement was performed in the present study, we cannot rule out the presence or effect of black carbon for this comparison which could help explain the underestimated sorption of higher-log K OW substances. Several studies (Accardi-Dey and Gschwend 2002;Koelmans et al 2006;Ghosh 2007;Brennan and Johnson 2017;Endo et al 2020) underpin the hypothesis that the widespread occurrence of black carbon may reduce in situ bioavailability and thereby lead to order-ofmagnitude discrepancies between measured in situ concentrations and EqP-computed porewater concentrations noted in the present and previous studies.…”
Section: Application Of Epsms To Baltic Sea Sedimentsmentioning
confidence: 59%
“…By definition, a toxic unit is the bioavailable concentration of a single PAH (i.e., C free in porewater), divided by the corresponding final chronic value. Alternatively, EPSMs can be used to determine the C free of PAHs, directly avoiding the need to invoke EqP assumptions that can significantly overstate bioavailability due to increased sorption capacities of heterogeneous carbonaceous phases in sediments (Apell and Gschwend 2016; Brennan and Johnson 2017). Guidance has also been developed for applying this procedure to derive porewater‐based remediation goals (US Environmental Protection Agency 2017a).…”
Section: Introductionmentioning
confidence: 99%